Tinggalan Arkeologi Di Pura Puseh Lan Bale Agung Tampuagan, Kecamatan Tembuku, Kabupaten Bangli - Agus Weda Prayudi, Putu; Redig, I Wayan; Sapta Jaya, Ida Bagus (Humanis; Vol 17 No 3 (2016), 2016)
Archeological heritage in Bali still functional and kept scares by the public by placing them in a temple, one of them is Puseh lan Bale Agung Tampuagan Temple, District of Tembuku, Bangli regency. The previous research conducted by the Institute for Preservation of Cultural Bali-NTB-NTT in 2001, discovered only to the extent of conservation or has not reached the stage of in-depth analysis. The objective of this study is to determine the form, period, and function of the archaeological heritage found Puseh lan Bale Agung Tampuagan Temple, Tembuku district, Bangli regency. The research method used in this study is the functional theory and the theory of religion. The first stage of method used to solve problems in this study is by collecting data through observation, interview, and library research. The second stage is data processing and analyzing data using qualitative, iconography, and contextual analysis. Based on the analysis, the conclusions are drawn in the form of archaeological heritage of 1 caturkaya statue that looks simple, 2 embodiment statues of bhatara, 5 embodiment statues of bhatari, 1 lingga tribhaga, 1 lingga above the lapik and stela, 1 fragment of lingga, 1 fragment of Ganesha statue, 4 fragments of statues, and fragments of buildings including 1 piece of building fragment above the lapik, 1 piece waterless building fragment, and 2 pieces of building fragments that might be a pillar. Archaeological heritage in Pura Puseh lan Bale Agung Tampuagan can be incorporated into the century of period Bali Madya because it has the characteristics of a style that was similar to the statue of Bali Madya contained in Puncak Penulisan Temple, the statue of the Bhatara in Sibi Agung Kesian Temple, statues pairs in Subak Taulan Kerobokan Temple, and the statue of the bhatari in Penataran Sasih Pejeng Temple. Archaeological heritage in Puseh lan Bale Agung Tampuagan Temple, Tembuku district, Bangli regency is still used as a means of worship by penyungsung temple. Societies or penyungsung temple consider that the archaeological heritage has religious power, magic, that on a certain day ceremony was held veneration of the archaeological heritage. The storage pelinggih penyimpen arca is trusted by the community as a means to seek refuge, safety, and fertility to plants and animals domesticated cattle community.